Honesty in Indonesian Literature - B. B. Dwijatmoko; B. Ria Lestari (Proceedings of AICS - Social Sciences, 2016)
As a reflection of human experience (Meyer, 1997; Dubey, 2013), literature reflects the values which a society holds. Indonesian literature, therefore, may also reflect honesty, an important value in a society, in the literature of Indonesian people. This research is a corpus study on honesty in Indonesian literature. This study aims at knowing the meaning of honesty in Indonesia as it is reflected in its literature and identifying the motivations which drive Indonesian people to be honest. The data are sentences which use the word jujur 'honest', kejujuran 'honesty', and sejujurnya 'honestly'. The analysis reveals that honesty falls into two types, namely verbal honesty and behavioral honesty. The analysis also reveals the motivations that drive Indonesian people to talk and behave honestly.